Evaluating physician concordance in interpretation of tracheobronchomalacia diagnosis and phenotyping using dynamic expiratory chest computed tomography - G. A. Cortes-Puentes; M. Matatko; B. J. Bartholmai; E. S. Edell; K. G. Lim (Scientific Reports)
Abstract Tracheobronchomalacia (TBM) presents diagnostic challenges due to its nonspecific symptoms and variability in diagnostic methods. This study evaluates physician concordance in TBM diagnosis and phenotyping using chest computed tomography (CT) scans with dynamic expiratory views. We conducted a retrospective cross-sectional study at Mayo Clinic Rochester, analyzing 150 patients with dynamic expiratory CT scans. Three specialists—a thoracic radiologist, a bronchoscopist, and a pulmonologist—reviewed identical CT scans, blinded to prior interpretations. Inter-rater agreement was assessed using Fleiss’s Kappa for TBM diagnosis and Cohen’s Kappa for TBM phenotype classification into six categories: No TBM, Excessive Dynamic Airway Collapse (EDAC), Crescent Type, Circumferential Type, Saber-Sheath Type, and Mixed Type. Among the 150 patients, 54 (36%) were diagnosed with TBM or EDAC. TBM was more prevalent in males, older individuals, and smokers. Agreement among specialists was substantial for TBM diagnosis (Fleiss’s Kappa = 0.61, p < 0.001) but moderate for phenotype classification (Fleiss’s Kappa = 0.52, p < 0.001). The highest concordance was between the thoracic radiologist and the pulmonologist (Cohen’s Kappa = 0.68), while the lowest was between the bronchoscopist and other specialists. There is substantial agreement in TBM diagnosis using chest CT scans with dynamic expiratory views, but moderate variability in phenotyping. Standardizing criteria and integrating pulmonary function testing could enhance diagnostic consistency and clinical relevance.